Alimentación Saludable: Líquidos - Linda B. Bobroff; Luisa Oliver-Cordero (EDIS)
Revised! FCS-8569-Span, a 3-page factsheet by Linda Bobroff and Luisa Oliver-Cordero, is the Spanish version of "Healthy Eating for Elders: Fluids" (FCS8569/FY070). It explains the importance of remaining well-hydrated, lists symptoms of dehydration, and gives tip on how to consume adequate fluids. Revised to expand content and references. Published by the UF Department of Family, Youth and Community Sciences, March 2007.